Patient preferences regarding communication of minor surgery results: who and how?. Issue 5 (2nd May 2022) - Senaratne, Radha; Casey, Máire-Caitlín; Balakrishnan, Theogren; Hussey, Alan; Jones, Deirdre; McInerney, Niall; Regan, Padraic J; Kelly, Jack L
Abstract : Background/Aims: The excision of skin lesions is one of the most common procedures in plastic surgery. Following the disruptions associated with the COVID-19 pandemic, this study investigated patient preferences communicating the results of skin lesion excision surgery. Methods: A retrospective analysis was conducted with patients who had undergone elective minor surgical procedures over a 30-day period. A questionnaire was distributed to 103 patients to assess their preferences regarding delivery of the outcomes of their procedure in terms of which healthcare professional contacted them and whether this occurred in person or remotely. The outcomes of this were used to adapt the service and a repeat analysis was conducted 3 months later. Results: If the lesion was benign, 45.0% of participants preferred to be contacted via email, letter or text, while 38.8% preferred either a telephone call or in-person appointment with their GP, and only 16.3% preferred direct contact from their hospital doctor. If the lesion was malignant, 55.0% preferred to be contacted by their GP, 30.0% by their hospital doctor and 15.0% via letter, email or text. The repeat analysis saw the proportion of patients who received their results via remote consultation with a hospital clinician increase from 12.8% to 16.1%, while the proportion of patients who received their results at an in-person outpatients appointment decreased from 14.5% to 9.3%. Conclusions: This study shows that a substantial proportion of patients would prefer to receive the results of skin lesion surgery from their GP over the telephone, suggesting that this would be a better means of delivering results than an in-person hospital appointment. This method could also reduce the number of patients returning to the clinic in person, helping to streamline follow up and improve clinic efficiency.